LUCAS (lung ultrasonography in cardiac surgery) score to monitor pulmonary edema after congenital cardiac surgery in children. (19th March 2022) - Girona-Alarcón, M.; Cuaresma-González, A.; Rodríguez-Fanjul, J.; Bobillo-Perez, S.; Inarejos, E.; Sánchez-de-Toledo, J.; Jordan, I.; Balaguer, M.
Abstract: Aim: Cardiopulmonary bypass (CPB) generates a systemic capillary leak syndrome with pulmonary edema. Lung ultrasound (LUS) could be useful to monitor it. Primary objective was to compare sensitivity, specificity, positive and negative predictive values of chest X-ray and LUS to detect pulmonary edema using a new score (LUCAS). Secondary objectives were to evaluate correlation between LUCAS score and respiratory and inotropic support. Methods: Prospective intervention study including patients <2 months admitted to the Pediatric Intensive Care Unit after CPB. LUS was performed with a lineal probe, screening 3 points in each lung (parasternal, anterolateral and posterior area), pre and post-CPB. Pulmonary edema was evaluated clinically, through LUCAS score and with X-ray. Results: 17 patients were included. LUS achieved higher sensitivity than X-ray to detect pulmonary edema (91.7 versus 44.0%) and greater predictive negative value (88.2 versus 53.3%). There was correlation between higher LUCAS score prior to surgery and longer mechanical ventilation. High values of LUCAS score after surgery correlated with longer CPB time, inotropic support, and FiO2 need. Conclusion: LUS detected pulmonary edema better than chest X-ray, with greater sensitivity and negative predictive value. LUCAS score was useful to predict more inotropic support and longer mechanical ventilation. Key notes: Cardiopulmonary bypass during cardiac surgery, generates a systemic capillary leak syndrome with pulmonary edema. In this prospective study performed in the Pediatric Intensive Care Unit, lung ultrasound detected pulmonary edema better than X-ray, with greater sensitivity and negative predictive value. LUCAS score was useful to predict more inotropic support and longer mechanical ventilation.